Considérer les enjeux d’un enseignement de la philosophie avant le lycée, en France, au prisme de la prudence intellectuelle - Marie Coasne-Khawrin (Éducation et Socialisation)
A contemporary movement promotes the introduction of children and adolescents to philosophy. By considering that philosophy should be introduced from primary school, in order to contribute to the intellectual education of the younger generation, this movement re-examines the role and place of philosophy in education. This article explores this project through the notion of intellectual prudence. It suggests a return to the Aristotelian concept of prudence, phronesis, to clarify the project of the pioneers of philosophy for children (Lipman and Sharp), but defends an updating of the notion in order to understand the contemporary educational stakes of early philosophy teaching. To do so, it combines a textual analysis, questioning this project from a reading of the works that gave rise to it, and a field philosophy approach, questioning their realization from the experience of an actual field of practices developed in this line in France.